Preparation method of modified Lax-TiNb2O7, modification application of rare earth metal La and lithium ion battery

By modifying Lax-TiNb2O7 as the negative electrode material of lithium-ion batteries, the problem of reduced capacity of lithium-ion batteries in the prior art under low temperature and fast charging conditions is solved, and a battery with high cycle life and low temperature performance is achieved.

CN119612591APending Publication Date: 2025-03-14BAICHENG NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411822361.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Under low temperature and fast charging conditions, the negative electrode material graphite will cause huge polarization, resulting in a decrease in battery capacity and forming irreversible lithium dendrites, resulting in loss of active lithium and rapid attenuation of capacity.

Method used

Modified Lax-TiNb2O7 (Lax-TNO) is used as the negative electrode material, and Lax-TNO with a microspheric structure is formed by adding tetrabutyl titanate, niobium chloride and polyoxyethylene-polyoxypropylene-polyoxyethylene to anhydrous ethanol, combined with lanthanum nitrate.

Benefits of technology

The stable cycle performance of lithium-ion batteries under low temperature conditions was achieved, with a capacity of 94% and a capacity reduction rate of 100 cycles at 2C, and the capacity reduction rate per cycle is only 0.014%, which significantly improves the cycle life and low temperature performance of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of modified Lax-TiNb2O7, modification application of rare earth metal La and a lithium ion battery, and the preparation method comprises the following steps: A, adding tetrabutyl titanate C16H36O4Ti, niobium chloride NbCl5 and polyoxyethylene-polyoxypropylene-polyoxyethylene F127 into absolute ethyl alcohol, and stirring to obtain a solution; b, adding lanthanum nitrate into the solution to obtain a mixed solution; c, storing the mixed solution at 180 DEG C for 12 hours; d, centrifugally collecting precipitates, and drying the precipitates in vacuum at 70 DEG C for 12 hours; and E, sintering in the air at 800 DEG C for 5 hours to obtain the modified Lax-TiNb2O7 with a microsphere structure, namely Lax-TNO. And a reasonable scheme is provided for the design of the high-surface-capacity battery in the cold area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of chemical raw materials for lithium ion batteries, and in particular to a modified La x -Preparation method of TiNb2O7, modification application of rare earth metal La and lithium-ion battery. Background Art

[0002] Lithium-ion battery is a rechargeable battery that relies on the movement of lithium ions between the positive and negative electrodes to work. It is a new type of modern green energy storage device with superior energy density, operating voltage, safety, and good cycle life. It is currently widely used in electric vehicles and electronic devices.

[0003] In the existing technology, graphite is the most commercialized negative electrode material, but the graphite negative electrode will produce huge polarization under low temperature and fast charging conditions, which will significantly reduce the battery capacity. In addition, due to the low working voltage of the graphite negative electrode, irreversible lithium dendrites (i.e. "dead lithium") will be formed, resulting in the loss of active lithium and rapid decay of capacity, especially in cold regions. Therefore, there are also research and development in the market to circumvent these shortcomings and seek more alternative materials. Summary of the invention

[0004] The invention discloses a modified La x -Preparation method of TiNb2O7, modification application of rare earth metal La and lithium-ion battery.

[0005] The present invention provides a modified La x -The preparation method of TiNb2O7 comprises the following steps:

[0006] A. Add tetrabutyl titanate C to anhydrous ethanol 16 H 36 O4Ti, niobium chloride NbCl5 and polyoxyethylene-polyoxypropylene-polyoxyethylene F127 are stirred to obtain a solution;

[0007] B. adding lanthanum nitrate to the solution to obtain a mixed solution;

[0008] C. storing the mixed solution at 180° C. for 12 hours;

[0009] D. Collect the precipitate by centrifugation and dry it under vacuum at 70°C for 12 h;

[0010] E. After sintering in air at 800°C for 5 hours, a modified La with a microspherical structure was obtained. x -TiNb2O7, namely La x -TNO.

[0011] Preferably, the step A is specifically as follows: adding 2.5 mmol tetrabutyl titanate, 5 mmol niobium chloride and polyoxyethylene-polyoxypropylene-polyoxyethylene into 20 ml of anhydrous ethanol, and stirring for 6 hours to obtain a solution.

[0012] Preferably, the input amount of F127 is 10% of the total raw material mass.

[0013] Preferably, the atomic molar ratio of the solution to the lanthanum nitrate is 1:0.01, 1:0.015 or 1:0.02; and x is 0.01, 0.015 or 0.02.

[0014] Preferably, x is 0.015.

[0015] Preferably, the degree of polymerization of F127 is 13,000.

[0016] Preferably, the modified La x -TiNb2O7 is a microsphere structure composed of particles, with a particle spacing of 20-40nm and a microsphere diameter of 2-5μm.

[0017] The present invention also provides a modified application of rare earth metal La, using lanthanum nitrate under the conditions of polyoxyethylene-polyoxypropylene-polyoxyethylene with a polymerization degree of 13000, tetrabutyl titanate and niobium chloride to synthesize La with a microsphere structure. x -TNO.

[0018] The present invention also provides a lithium ion battery, comprising: selecting the modified La x La prepared by the preparation method of TiNb2O7 x -TNO is the negative electrode and lithium iron phosphate is selected as the cathode.

[0019] Preferably, the x is 0.015, the La x -TNO is a microsphere structure.

[0020] Preferably, at room temperature, 20°C, the cycle is 2000 times / time; at -30°C, 2°C, the cycle is 100 times / time.

[0021] The advantages of the present invention are as follows: the structure formed by using tetrabutyl titanate, niobium chloride and polyoxyethylene-polyoxypropylene-polyoxyethylene in combination with lanthanum nitrate is microspherical, and the ion and electron conductivity are strong. The lithium ion battery produced has an excellent cycle life of 2000 cycles, and the capacity decrease of each cycle is only 0.014%. At minus 30°C, it is still stable, and can reach 100 cycles at 2C, and the capacity retention reaches 94%. An excellent solution is proposed for the design of high surface capacity batteries in cold areas.

[0022] La x-TNO has good safety and high rate performance, as well as good structural reversibility and high lithium insertion and extraction potential, which ensures the stability of the structure and effectively avoids the common problems of SEI film and Li dendrite formation that affect lithium-ion batteries. DETAILED DESCRIPTION

[0023] The invention discloses a modified La x -Preparation method of TiNb2O7, modification application of rare earth metal La and lithium-ion battery.

[0024] The following is a clear and detailed description of the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] A modified La of the present invention x -The preparation method of TiNb2O7 comprises the following steps:

[0026] A. Add tetrabutyl titanate C to anhydrous ethanol 16 H 36 O4Ti, niobium chloride NbCl5 and polyoxyethylene-polyoxypropylene-polyoxyethylene F127 are stirred to obtain a solution;

[0027] B. adding lanthanum nitrate to the solution to obtain a mixed solution;

[0028] C. storing the mixed solution at 180° C. for 12 hours;

[0029] D. Collect the precipitate by centrifugation and dry it under vacuum at 70°C for 12 h;

[0030] E. After sintering in air at 800°C for 5 hours, a modified La with a microspherical structure was obtained. x -TiNb2O7, namely La x -TNO.

[0031] Preferably, the step A is specifically as follows: adding 2.5 mmol tetrabutyl titanate, 5 mmol niobium chloride and polyoxyethylene-polyoxypropylene-polyoxyethylene into 20 ml of anhydrous ethanol, and stirring for 6 hours to obtain a solution.

[0032] Preferably, the input amount of F127 is 10% of the total raw material mass (ie 10% of the total drug mass).

[0033] Preferably, the atomic molar ratio of the solution to the lanthanum nitrate is 1:0.01, 1:0.015 or 1:0.02; and x is 0.01, 0.015 or 0.02.

[0034] Preferably, x is 0.015.

[0035] Preferably, the degree of polymerization of F127 is 13,000.

[0036] Preferably, the tetrabutyl titanate, TBT, Macklin, has a purity of ≥99.0%.

[0037] Preferably, the niobium chloride, NbCl5, Macklin, has a purity of 99%.

[0038] The present invention also provides a modified application of rare earth metal La, using lanthanum nitrate under the conditions of polyoxyethylene-polyoxypropylene-polyoxyethylene with a polymerization degree of 13000, tetrabutyl titanate and niobium chloride to synthesize La with a microsphere mesoporous structure. x -TNO.

[0039] The present invention further provides a lithium ion battery, comprising: selecting the modified La x La prepared by the preparation method of TiNb2O7 x -TNO is the negative electrode and lithium iron phosphate is selected as the cathode.

[0040] Preferably, x is 0.015.

[0041] Preferably, at room temperature and 20° C., the cycle is 2000 times / time; at -30° C. and 2° C., the cycle is 100 times / time. The terms “a” and “times” have the same meaning in this application.

[0042] Prior to this application, the use of pure TNO (i.e. TiNb2O7) in lithium-ion batteries had good advantages, but also obvious disadvantages: 4+ and Nb 5+ The ions are randomly distributed on the octahedral sites connected by the corners of TiNb2O7; the disadvantage is that the band gap is large, which easily produces a large charge transfer barrier, especially at low temperatures, which will lead to Li + It cannot pass quickly. Secondly, the low electronic conductivity causes the electrode potential to deviate from the equilibrium point during the cycle, resulting in electrochemical polarization, reducing the effective point, affecting the available lithium ions, and the area capacity is limited, and the low-temperature performance adaptability is poor.

[0043] The present application also abandons the traditional modification method of TiNb2O7 and adopts an innovative method different from the prior art.

[0044] The technology of this application provides a new solution for fast-charging batteries with long cycle life, and can be widely used in low-temperature areas. x La prepared by the preparation method of TiNb2O7 x -TNO is used as the negative electrode and lithium iron phosphate is selected as the cathode to form a lithium-ion battery.

[0045] La x -TNO has high capacity, good structural reversibility, and high lithium insertion and extraction potential, which can ensure its structural stability and avoid the formation of SEI film and Li dendrites.

[0046] TiNb2O7 is modified to make La x -TNO is evenly dispersed in porous microspheres, with gaps between microspheres. At the same time, the particles in the microspheres also have a spacing of 20-40nm, and the spacing between the lattices that make up the particles is only 0.272-0.275nm. Therefore, when used in lithium-ion batteries, La x -TNO particles are very stable, and the distance between particles is stable, which can form channels for lithium ions. The ion diffusion barrier is reduced, so that lithium ions have more paths to move and move faster, fewer lithium ions are blocked, and the electrode material and electrolyte can fully contact each other, so that La x -The ionic and electronic conductivity of TNO microspheres are significantly enhanced, and the cycle life cycle advantage is strong.

[0047] Again, La x -TNO, the orbits between La-3d and O-2p state electrons overlap, forming a pd hybrid space, forming an impurity energy band, shortening the band gap, reducing the band gap, and widening the Li + The diffusion channel of lithium ion batteries can be further improved.

[0048] When x is 0.015 mol, that is, La 0.015 -TiNb2O7, with excellent rate performance and long cycle stability, at 20C, it is 192.8mA h g-1, and the capacity value after 2000 cycles is 203.1mA h g-1, which achieves the improvement of the pseudocapacitive effect of TiNb2O7 in fast charging and reduces the diffusion energy barrier.

[0049] Example

[0050] Modified La x - A method for preparing TiNb2O7, wherein x is set to represent the molar number of La atoms, and x=0.01, 0.015 or 0.02, comprises the following steps:

[0051] (A1) Add 2.5 mmol of tetrabutyl titanate, 5 mmol of niobium chloride and 10% of the total raw material mass of F127 to 20 ml of anhydrous ethanol and stir for 6 hours to obtain a solution.

[0052] (B1) When x of La is 0.01, 0.015 or 0.02, lanthanum nitrate in atomic molar ratios of 1:0.01, 1:0.015 and 1:0.02 are added to the solution to obtain a mixed solution.

[0053] (C1) The mixed solution was transferred to an oven and stored at 180°C for 12 h. The resulting precipitate was collected by centrifugation and then dried under vacuum at 70°C for 12 h.

[0054] (D1) After sintering at 800℃ in air for 5 hours, La x -TNO(x=0.01, 0.015, 0.02).

[0055] The harvested La x -TNO (x=0.01, 0.015, 0.02) was compared, and x was preferably 0.015.

[0056] Comparison Example

[0057] The control example adopts the same preparation process as above, but does not add F127 and lanthanum nitrate.

[0058] TNO and La x -TNO comparison results:

[0059] Confirm that the La prepared in this application x -TNO is an impurity-free phase, that is, there are no impurities such as La(NO3)3, TiO2 or Nb2O5, etc.

[0060] La prepared by the raw materials and method of the present invention x -TNO, x = 0.01, 0.015, 0.02. When x = 0.015, the position angle of the diffraction peak is smaller, and the lattice expands, that is, La 3+ Well doped into the gaps of the TNO lattice, forming a crystal lattice expansion. When x = 0.01 and 0.02, Li + The stability is not as good as x=0.015.

[0061] La prepared by the raw materials and method of the present invention x -TNO, when x = 0.015, La 0.015 -TNO has an excellent large unit cell volume, which can provide a wider Li + Transport pathways, promoting Li + diffusion.

[0062] Therefore, by comparison, La 0.015 -TNO has a larger and more suitable volume unit, Li + Diffusion provides a wider pathway to accelerate Li + Diffusion dynamics, that is to say, when it is used as a raw material for lithium batteries, the effect is better and the durability is stronger.

[0063] La 3+ The doping modification of La can effectively enlarge the interplanar spacing of TNO, which is helpful for Li+ diffusion. 3+ The La-doped TiNb2O7 functional coating, which is in situ doped into the TNO lattice, is used to balance the ion-electron transport of the graphite anode for fast-charging lithium-ion batteries.

[0064] La prepared by the raw materials and method of the present invention x -TNO, under the microscope, appears as a large number of small-size monodisperse microspheres, which are composed of interconnected nanoparticles (particles). x -TNO exists in a small amount of titanium dioxide on the surface of the microspheres to repel Ti 4+ , thereby effectively improving Li + movement.

[0065] La x -TNO microspheres have a diameter of 2-5 μm, a particle spacing of 20-40 nm, and a lattice spacing of 0.272-0.275 nm. 0.015 -TNO's microsphere structure is well matched and has good crystallinity.

[0066] 1C means charging and discharging for 60 minutes each, and 2C means charging and discharging for 30 minutes each.

[0067] Under the same conditions, the capacity of the unmodified TNO electrode at 2C is 101mAg -1 , La 0.015 -TNO electrode has a capacity of 254.41 mAh g at 2C -1 , La 0.01 -TNO electrode has a capacity of 201 mAh g at 2C -1 , La 0.02 -TNO electrode has a capacity of 140 mAh g at 2C -1 , it can be seen that under the same circumstances, La 0.015 -TNO electrode has a more stable current density surface and stronger cycle capacity, because La allows ions to have a wider diffusion path, making Li + The diffusion effect is very good, and the capacity loss per cycle is as low as 0.053%.

[0068] The La of the present invention0.015 -TNO, under the modification of La, makes TNO obtain a very large interplanar spacing, which is Li + Diffusion provides the widest channel, thereby improving the initial charge and discharge capacity.

[0069] At any current density, La 0.015 -TNO has a higher capacity than TNO. However, since TNO anode is prone to polarization during the cycle and its polarization is high, it is not conducive to the durability of lithium-ion batteries. 0.015 -TNO can effectively maintain a stable cycle effect, has a strong anti-polarization effect, and accelerates Li + The transfer rate can improve the electrochemical performance of the electrode.

[0070] When tested at 0.2C, La 0.015 -TNO is 301.7 mAg h -1 Then, after the lithium-ion battery was tested and used continuously for many times, when the current density was set to 0.2C, La 0.015 -TNO is 288.7mAgh -1 , close to the initial capacity, with excellent reversibility.

[0071] Visible La x -TNO has huge commercial application capabilities, La 0.015 -TNO is better.

[0072] = Increase in unit cell volume caused by La doping modification, Li + The wider the diffusion channel in the crystal, the more Li + The easier it is to migrate. 0.015 -TNO has good electrical conductivity and low Li + Diffusion barrier, so that L i+ Super fast transfer.

[0073] Regarding lithium-ion batteries, using La x -TNO is used as the negative electrode and lithium iron phosphate is used as the cathode to form a full battery. From the above content, it can be seen that the present invention discloses a very promising high-performance negative electrode material.

[0074] La x -TNO widens the interplanar spacing and has good cycle reversibility under different temperature conditions, improving the Li + Diffusion rate, especially La 0.015 -TNO also has superior reversible capacity and lifespan at low temperatures.

[0075] Therefore, it can be seen that La 3+Doping modification can enhance electronic conductivity and form a TNO structure with faster ion transport channels. 3+ After doping, the ion migration rate increases, the diffusion barrier decreases, and the conductivity increases due to the increase in the material lattice spacing. The cycle life is 2000 cycles, and the capacity drop rate of each cycle is extremely low. At -30℃, La 0.015 -TNO performed 200 cycles at 2C and showed stable cycling performance with a capacity retention of 94.14%. It is a very advantageous fast charging battery solution with a long cycle life.

[0076] The above is a modified La provided by the present invention. x -The preparation method of TiNb2O7, the modified application of rare earth metal La and lithium-ion batteries are introduced in detail. For those skilled in the art, according to the ideas of the embodiments of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A modified La x - A method for preparing TiNb2O7, characterized in that: The following steps are involved: A. Add tetrabutyl titanate C to anhydrous ethanol 16 H 36 O4Ti, niobium chloride NbCl5 and polyoxyethylene-polyoxypropylene-polyoxyethylene F127 are stirred to obtain a solution; B. adding lanthanum nitrate to the solution to obtain a mixed solution; C. storing the mixed solution at 180° C. for 12 hours; D. Collect the precipitate by centrifugation and dry it under vacuum at 70°C for 12 h; E. After sintering in air at 800°C for 5 hours, modified La x -TiNb2O7, namely La x -TNO.

2. The modified La according to claim 1 x - A method for preparing TiNb2O7, characterized in that: The step A is specifically as follows: 2.5 mmol of tetrabutyl titanate, 5 mmol of niobium chloride and 10% of the total raw material weight of polyoxyethylene-polyoxypropylene-polyoxyethylene are added into 20 ml of anhydrous ethanol, and stirred for 6 hours to obtain a solution.

3. The modified La according to claim 1 x - A method for preparing TiNb2O7, characterized in that: The degree of polymerization of the F127 is 13,000.

4. The modified La according to claim 1 x - A method for preparing TiNb2O7, characterized in that: The atomic molar ratio of the solution to the lanthanum nitrate is 1:0.01, 1:0.015 or 1:0.02; and x is 0.01, 0.015 or 0.

02.

5. The modified La according to claim 4 x - A method for preparing TiNb2O7, characterized in that: The x is 0.

015.

6. The modified La according to claim 1 x - A method for preparing TiNb2O7, characterized in that: The modified La x -TiNb2O7 is a microsphere structure composed of particles, the diameter of the microsphere is 2-5μm, and the particle distance is 20-40nm.

7. A modified application of rare earth metal La, characterized in that: The La microsphere structure of any one of claims 1 to 6 is synthesized by using lanthanum nitrate in the presence of tetrabutyl titanate, niobium chloride, and polyoxyethylene-polyoxypropylene-polyoxyethylene with a polymerization degree of 13000. x -TNO.

8. A lithium ion battery, characterized in that: include: Select the modified La described in any one of claims 1 to 6 x La prepared by the preparation method of TiNb2O7 x -TNO is the negative electrode and lithium iron phosphate is selected as the cathode.

9. The lithium-ion battery according to claim 8, characterized in that: The x is 0.

015.

10. The lithium ion battery according to claim 8, characterized in that At room temperature, 20°C, cycle 2000 times; at -30°C, 2°C, cycle 100 times.

Citation Information

Patent Citations

  • Preparation of titanium niobium oxide lithium ion battery negative electrode material based on high oxidation state ion doping

    CN115744986A

  • Modified titanium niobate coated ternary positive electrode material as well as preparation method and application thereof

    CN118579855A